Clinical Evaluation and Assessment of Laser Irradiation on the Stability of Orthodontic Implant: A Prospective Experimental Study - Namrata Shehare; Suchita Daokar; Dhananjay Ghunawat; Harsha Kaurani (Dentistry and Medical Research, 2024)
Background: Currently, the orthodontic implants have reached to a peak where they are considered a dependable modality to provide temporary supplemental anchoring in orthodontic therapy. When absolute anchoring is a necessity or in cases of minimally cooperative patients, these devices can help to manage skeletal anchorage. However, its failure is a major complication that occurs during orthodontic treatment which is multifactorial. The stability of the mini-implant is crucial to the outcome of orthodontic intervention. Approaches to increasing the stability of the mini-implant were researched. Hence, this study was carried out to compare and contrast and clinically assess the integrity of orthodontic implants over time. Subjects and Methods: Split-mouth technique of treatment was carried out on 16 patients, i.e., one side of the mandible was considered the experimental group (implant site irradiated with laser after placement) and the other was considered the control side (implant site not irradiated with the laser). Titanium mini-implants of the dimensions 1.5-mm diameter and 6-mm length were employed in the present study. They were positioned in the interradicular space between the first molar and second premolar in the mandibular posterior region, 7-mm apical to the alveolar crest. During the whole process, the laser utilized was a multimode GaAs diode laser with a wavelength of 980 nm. It had 0.5–10W output power which was adjustable with the frequency of 1–20 kHz and its main body input voltage was DC12 To further analyze the stability of the implant which in turn would aid in success assessment, the resonance frequency concept was utilized. The readings were recorded (T0) after insertion, (T1) 24 h after insertion, (T2) 2 weeks after insertion, (T3) 4 weeks after insertion, (T4) 6 weeks after insertion, and (T5) 8 weeks after insertion. The higher the implant stability quotient values the greater the stability and hence the optimal loading time. Results: The test employed for statistical analysis was Mann–Whitney U, Kruskal–Wallis, and ANOVA test. After analysis of all the readings, it was found that low-level laser therapy has a significant role in the stability of orthodontic mini-implant. Conclusion: Findings from this study suggest that low-level laser irradiation at the time of implant placement controls the inflammatory reaction around the implant and improves its stability.